Hubungan antara Obesitas dengan Penurunan Fungsi Faal Paru pada Polisi Wanita di Polda Jawa Timur: [Obesity and the Decrease of Pulmonary Function Test in Policewomen in East Java, Indonesia] - Christina Hardono; Benjamin Palgunadi Margono (Faculty of Medicine Universitas Airlangga, 2015)
Background: The prevalence of obesity is increasing in Indonesia, and there is evidence that obesity, in particular abdominal obesity as a marker of insulin resistance, is negatively associated with pulmonary function. The mechanism for this association and the best marker of abdominal adiposity in relation to pulmonary function is not known. Study objectives: We assessed the association between pulmonary function (ie, FEV1 and FVC) [with maneuvers performed in the sitting position] with adiposity markers (ie, body mass index (BMI) and waist circumference (WC), as markers of adiposity and body fat distribution in Policewomen in East Java Police Departement. We used paired student t test to analyze the association of pulmonary function and abdominal adiposity markers. Design: Observational cross sectional analytic study. Setting and participants: A random sample of policewomen (n = 120) from the general population East Java Police Departement, 20 to 45 years of age, who fulfill inclusion criterion of this study. Results: The measures of adiposity (ie. Waist circumference and BMI) were not significantly related to %FEV1 and %FVC after analyzed with correlation Pearson and Spearman test (p > 0.05). Conclusion: BMI categories and waist circumference (WC) were not associated with FEV1 percent predicted and FVC percent predicted, may be the physical activity twice a week can maintain health status.